Synthesis and magnetic properties of barium-calcium hexaferrite particles prepared by sol-gel and microemulsion techniques - Jotania, R. B.; Khomane, Ramdas B.; Chauhan, C. C.; Menon, Shamal K.; Kulkarni, B. D. (Journal of Magnetism and Magnetic Materials, 2008)
The preparation of W-type hexaferrite particles with the composition BaCa2Fe16O27 by microemulsion and a stearic acid sol - gel method with and without surfactant has been investigated at various sintering temperatures. The structural and magnetic characteristics have been studied by X-ray diffraction ( XRD), a vibrating sample magnetometer ( VSM), scanning electron microscopy ( SEM), thermogravimetric analysis ( TGA), differential scanning calorimetric ( DSC) and Fourier transform infrared ( FTIR) techniques. The effect of sintering temperature on the properties of BaCa2Fe16O27 hexaferrites has been studied. The value of saturation magnetization ( M-s) depends on types of surfactant used. The sample prepared in the presence of polyoxyethylene ( 20) sorbitan monooleat ( Tween 80) shows low saturation magnetization ( M-s 15.10 emu/g), whereas the other sample prepared in the presence of a surfactant cetyltrimethylammonium bromide (CTAB) exhibits high saturation magnetization (M-s = 24.60 emu/g) compared to the normal sample. (C) 2007 Elsevier B. V. All rights reserved.
Keywords: BaCa2Fe16O27; hexaferrite; magnetic property; Microemulsion; Sol-gel method; surfactant